Fasting Serum Insulin Level Among Overweight and Obese School Children - Haque, Mahmudul; Khan, Md Jahangir; Chowdhury, Mahmood A; Khaled, Md Saifuddin; Barua, Prasun (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: The rising prevalence of obesity in developing countries is largely due to rapid urbanization and mechanization which has led to reduction in the energy expenditure. It is accompanied along with an increase in energy intake due to increased purchasing power and availability of high fat, energy dense fast food. A high prevalence of obesity in children can be attributed to the lack of knowledge about adverse effects of unhealthy nutrition in urban school children in Bangladesh. So there is a need to identify overweight and obesity as one of the risk factors leading to condition of metabolic syndrome and or central obesity and give baseline information to approach for its prevention at childhood with the assistance from continuation of medical research as early as possible. Methods: This was a case control study. A total of 100 subjects were included in this study. Among them 50 were considered as cases (Whose BMI was >85th percentile) and 50 were considered as controls (Whose BMI was > 5th percentile to 84th percentile). BMI were calculated by standard protocol used for children. Children suffering from DM, renal diseases and other endocrine diseases were excluded. Serum insulin, blood glucose, total cholesterol, LDL-C, HDL-C and TG were measured in all samples in fasting state. Insulin resistance was calculated by HOMA-IR value. Results: Result showed that serum insulin and HOMA-IR values were significantly higher in cases (Overweight and obese children) than in controls of same age and sex (p=<0.001). Result also showed that there were positive correlation among Total Cholesterol (p=<0.001), LDL-C (p=<0.001), TG (p=<0.001) and HOMA-IR value. Conclusion: We found that insulin resistance was strongly associated with metabolic syndrome and its components. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 21-24